1978
DOI: 10.1007/bf00302526
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chromosomes of workers exposed to acrylonitrile

Abstract: Examination of 18 workers who had been exposed to acrylonitrile for 15.3 years on average and 18 workers who had not been exposed to acrylonitrile showed no difference in the incidence of chromosome aberrations; for each person concerned 100 metaphases were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…The disagreement between the significance of the sister chromatid exchange frequency observed in this study and the lack of chromosome aberrations in lymphocytes of acrylonitrile-exposed workers (14) is probably due to differences in experimental conditions and acrylonitrile doses « 20 ppm for the exposed workers).…”
Section: Referencescontrasting
confidence: 77%
See 1 more Smart Citation
“…The disagreement between the significance of the sister chromatid exchange frequency observed in this study and the lack of chromosome aberrations in lymphocytes of acrylonitrile-exposed workers (14) is probably due to differences in experimental conditions and acrylonitrile doses « 20 ppm for the exposed workers).…”
Section: Referencescontrasting
confidence: 77%
“…This monomer is widely used as an intermediate in the manufacture of synthetic fibers, plastics, and rubbers and as a grain fumigant, and it has been shown to have mutagenic power in assay systems utiliz-0355-3140/82/040290-04USD2.00 ing bacterial cells (7,17) and carcinogenic activity in animals (6,15,16). Furthermore, acrylonitrile is toxic and a suspected carcinogen to man (4), even if negative results have been obtained concerning its genotoxic action in cytogenetic studies on mice and rats (11) and in epidemiologic investigations carried out with exposed workers (14).…”
mentioning
confidence: 99%
“…Early epidemiological studies have suggested that AN may increase the incidence of lung, colon, and stomach cancers among exposed workers (Thiess and Fleig, 1978;Blair et al, 1998). However, recent studies suggested that there is no significant association between human exposure to AN and carcinogenicity (Benn and Osborne 1998;Swaen et al, 1998;Wood et al, 1998;IARC, 1999;Marsh et al, 2001;Schulz et al, 2001).…”
Section: Acrylonitrile (Anmentioning
confidence: 99%
“…However, there are no reliable in vivo data supporting positive mutagenicity of AN to humans and mammals. Thiess and Fleig (1978) 66) studied whether of not chromosomal aberrations of peripheral lymphocytes would increase in workers exposed to 1.5-5 ppm (estimated levels) of AN for an average of 10-15 years, and found no changes in the incidence of chromosomal aberrations. Rabello-Gay and Ahmed (1980) 67) showed that treatment of mice orally with 7-21 mg/kg/day of AN for 4-30 days did not result in increased chromosomal aberrations of bone marrow cells.…”
Section: Mutagenicitymentioning
confidence: 99%